Low Dosing Norepinephrine Effects on Cerebral Oxygenation and Perfusion During Pediatric Shock - Vedrenne-Cloquet, Meryl; Chareyre, Judith; Léger, Pierre-Louis; Genuini, Mathieu; Renolleau, Sylvain; Oualha, Mehdi (Frontiers in Pediatrics, 2022)
Background: Cerebral hypoperfusion and impaired oxygen delivery during pediatric critical illness may result in acute neurologic injury with subsequent long-term effects on neurodevelopmental outcome. Yet, the impact of norepinephrine on cerebral hemodynamics is unknown in children with shock. We aimed to describe the norepinephrine effects on cerebral perfusion and oxygenation during pediatric shock. Patients and methods: We conducted an observational multicentre prospective study in 3 French pediatric intensive care units. Children less than 18 years of age excluding traumatic brain injury were included in the study if they need norepinephrine for shock. Systemic and cerebral hemodynamics were compared between the time of initiation of norepinephrine (T0), and the steady-state (Tss). Cardiac output (CO) was measured using ultrasound. Cerebral perfusion was assessed on middle cerebral arteries (MCA) using transcranial doppler ultrasound. Cerebral tissue oxygen saturation (rScO2) was recorded using near infrared spectroscopy, and we calculated cerebral fractional tissue oxygen extraction (cFTOE = SpO2-rScO2/SpO2). Main results: Fourteen children (median[IQR] age of 3.5[1; 13.5] years) were included. Norepinephrine at 0.2[0.1; 0.32] μg/kg/min significantly increased mean arterial blood pressure (61[56 ; 73] mmHg at Tss versus 49[42;54] mmHg at T0, p=10^-3) without change of CO. MCA velocities, pulsatility index, rScO2, and cFTOE did not significantly change between T0 and Tss. Some individuals observed variations in estimated CBF, which slightly improved in 7 patients, remained unchanged in 5, and was impaired in 2. No patient experienced significant variations of rScO2. Conclusions: Low-dosing norepinephrine, despite a homogeneous and significant increase in arterial blood pressure, had little effects on cerebral perfusion and oxygenation during pediatric shock. This reinforces the need for personalized tailored therapies in this population.